Pertanggungjawaban Pelaku Tindak Pidana Pemalsuan Sertifikat Hak Milik Dalam Sesuatu Perjanjian Jual Beli Tanah Di Desa Sukarame (Studi Putusan Nomor 1099/Pid.B/2021/Pn Tjk) - Zaini, Zulfi Diane; Safitri, Melisa; Setiawan, Ifal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Forgery of letters is a criminal act containing factors of untruth or falsification of something (object), somethingthat appearsauthentic from the outsidewhilst in realityit's faropposite to the usage of the reality. The problemon thishave a look at is the decide's attention in passing a decisionat the perpetrators of the crime of forging letters and the crookobligation of the perpetrators of the crime of forging the Letter of evaluationselectionNo:1099/Pid.B/2021/PN.Tjk. The studiestechnique used is normative juridical in addition to empirical, due toexamining the choose's considerations in passing a choiceon theculprit of the crime of forging letters through Sujir Bin Karam, the selectionbecomeaccurateconsistent withsufficientproof and factdata. Method and criminalresponsibility from the meeting of the perpetrators of the crime of forgery of letters, where the perpetrators were legally and convincingly verified, the panel of judges sentenced the perpetrators to imprisonment for 2 years and 3 months